Denatonium benzoate bitter taste perception in chronic rhinosinusitis subgroups. Issue 6 (3rd September 2020) - Civantos, Alyssa M.; Maina, Ivy W.; Arnold, Monique; Lin, Cailu; Stevens, Elizabeth M.; Tan, Li Hui; Gleeson, Patrick K.; Colquitt, Lauren R.; Cowart, Beverly J.; Bosso, John V.; Palmer, James N.; Adappa, Nithin D.; et al.
Abstract : Background: Chronic rhinosinusitis (CRS) with nasal polyps (CRSwNP) and CRS without nasal polyps (CRSsNP), and aspirin‐exacerbated respiratory disease (AERD) have varying levels of inflammation and disease severity. Solitary chemosensory cells (SCCs) are enriched in nasal polyps, are the primary source of interleukin 25 (IL‐25) in upper airways, leading to type 2 inflammation, and are activated by bitter‐tasting denatonium benzoate (DB). Thus, we sought to evaluate DB taste perception at a range of concentrations in order to identify 1 that most differentiates CRS subgroups from controls. Methods: CRSsNP (n = 25), CRSwNP (n = 26), and AERD (n = 27) patients as well as controls (n = 25) tasted 6 DB concentrations in a fixed, random order, rating on a category scale of 0 (no intensity) to 12 (extremely intense). Sinonasal epithelial cultures were treated with and without denatonium and analyzed for IL‐25 via flow cytometry. Results: CRSsNP patients rated DB as significantly less intense than did controls at all concentrations: 5.62 × 10 –9 M, 1.00 × 10 –8 M, 1.78 × 10 –8 M, 3.16 × 10 –8 M, 5.62 × 10 –8 M, and 1.00 × 10 –7 M (all p < 0.0083). CRSwNP patients did not show significant differences from controls. AERD patients rated DB as significantly more intense than did controls at concentrations of 1.00 × 10 –8 M and 3.16 × 10 –8 M ( p < 0.0083). In vitro data demonstrated significant increase in IL‐25–positive cells after denatonium stimulation (n = 5), compared to control (n = 5) ( p = 0.012). Conclusion: Our findings link in vitro DB stimulation of sinonasal tissue with increased IL‐25 and show differential DB taste perception in CRS subgroups relative to the control group, with CRSsNP being hyposensitive and AERD being hypersensitive. We propose a concentration of 3.16 × 10 –8 M for future study of clinical utility.